Πρόσληψη διαιτητικών ινών και καρκίνος του παχέος εντέρου - Νικολάου, Ηλίας (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
Several epimiological studies have reported the protective effect of dietary fiber compare to chronic diseases. This issue has brought a considerable debate with many scientists argue as to whether this protective effect is connected to dietary fiber or dietary components in general. Colorectal cancer constitutes an emerging pathology disease with great impact in health on a global scale. Epidemiological studies indicated that there is an apparent connection among colorectal cancer and diets especially those in Western countries. In this prospective study it has been examined 40 academic journals the period between 1987-2014. Furthermore, epidemiological data have showed similar results. However genetists mention that colorectal cancer is a multivariate disease as well as various risk factors indicated in the development of malignant tumor. Those risk factors are being proposed as genes, age, ethnic background, inflammatory diseases and family history. From everything that has been extended above, it is apparent that dietary fiber indicate a partial protective affect especially those from cereals, whole grains and vegetables.
Keywords: Chronic diseases; Dietary fiber; Colorectal cancer; Διαιτητικές ίνες; Καρκίνος παχέος εντέρου; Παθολογικό νόσημα; Τρόφιμα ζωικής προέλευσης; Διατροφή